The Development of a Training Curriculum on Pruning and Canopy Management of Cashew for Cashew Farmers in Uttaradit Province - Daengngoen, Phanu; Kokong, Kasorn (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2026)
The objectives of this research were 1) to develop a training curriculum on pruning and canopy management for cashew farmers in Uttaradit Province, and 2) to study the effects of implementing the training curriculum in terms of knowledge, practical skills, and satisfaction with the curriculum. The sample consisted of 30 cashew farmers from Tha Pla and Nam Pat Districts, Uttaradit Province, selected through purposive sampling. The research instruments included the training curriculum, a knowledge achievement test, a practical skill evaluation form, and a satisfaction questionnaire. Data were analyzed using Mean ( ), Standard Deviation (S.D.), and dependent samples t-test. The research findings were as follows 1. The training curriculum was developed based on Taba’s model, initiating with a diagnostic study of problems and needs from both farmers and academic experts. This led to the design of a curriculum comprising six core components: principles, objectives, structures and contents, learning activities, media and materials, and evaluation, encompassing both theoretical and practical dimensions. The expert evaluation revealed that the curriculum’s overall appropriateness was at the highest level ( = 57, S.D.= 0.12), with an Index of Item-Objective Congruence (IOC) of 1.00 for all items. The curriculum implementation results indicated that: 1) the farmers’ average post-training knowledge and understanding scores were significantly higher than their pre-training scores at the .05 level; 2) the evaluation of practical skills passed the established criteria at the highest level; and 3) the farmers’ overall satisfaction with the training curriculum was at the highest level ( = 4.75, S.D. = 0.25).